The Potential of Purinergic Signaling to Thwart Viruses Including SARS-CoV-2 - Ferrari, Davide; Rubini, Michele; Burns, Jorge S. (Frontiers in Immunology, 2022)
A long-shared evolutionary history is congruent with the multiple roles played by purinergic signalling in viral infection, replication and host responses that can assist or hinder viral functions. An overview of the involvement of purinergic signaling among a range of viruses is compared and contrasted with what is currently understood for SARS-CoV-2. In particular, we focus on the inflammatory and antiviral responses of infected cells mediated by purinergic receptor activation. Although there is considerable variation in a patient's response to SARS-CoV-2 infection, a principle immediate concern in Coronavirus disease (Covid-19) is the possibility of an abarrent inflammatory activation causing diffuse lung oedema and respiratory failure. We discuss the most promising potential interventions modulating purinergic signalling that may attenuate the more serious repercussions of SARS-CoV-2 infection and aspects of their implementation.